A young girl with severe polyarteritis nodosa successfully treated with tocilizumab: a case report - Margaux Boistault; Mireia Lopez Corbeto; Pierre Quartier; Laura Berbel Arcobé; Ariadna Carsi Durall; Florence A. Aeschlimann (BMC, 2021)
Abstract Background Childhood Polyarteritis nodosa (PAN) is a systemic vasculitis with necrotizing inflammation of medium- and small-sized arteries. Disease evolution may be severe and refractory to standard treatment including prednisone, azathioprine and cyclophosphamide. Case presentation We present the case of a young girl with severe PAN resulting in progressive ischemia and necrosis of fingers and toes. Biological work-up revealed increased acute phase reactants and interleukin-6 levels. She was only partially controlled despite high-dose corticosteroids and cyclophosphamide infusions, and eventually achieved rapid improvement and sustained remission on tocilizumab. Further, we review the current evidence of the interleukin-6-inhibitor tocilizumab for the treatment of PAN. Conclusion Tocilizumab may be an efficient therapeutic option in a subset of treatment-refractory children with PAN.